2018
DOI: 10.3390/su10030835
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Common Ontology of Scaling Up in Development

Abstract: Scaling up development measures to target global food insecurity has a distinctly spatial character and is often cited as a solution to the global hunger crisis. Development does not occur without scaling and consensus on the ontological meaning of scaling up is a vital component to developing sustainable solutions to the global hunger crisis across geographical scales. Yet 'scaling up', while frequently used throughout Research and Development (R&D) and Natural Resource Management (NRM) literature, lacks onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Moore et al [30] argued that specific strategies and processes could be identified for each type of scaling depending on one's goals, but also acknowledged the cross-cutting nature of these strategies. The approach of distinguishing between strategies for different types of scaling can also be seen in previous models and frameworks [19], or in papers that are attempting to develop "success strategies" for different types of scaling [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moore et al [30] argued that specific strategies and processes could be identified for each type of scaling depending on one's goals, but also acknowledged the cross-cutting nature of these strategies. The approach of distinguishing between strategies for different types of scaling can also be seen in previous models and frameworks [19], or in papers that are attempting to develop "success strategies" for different types of scaling [17].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the current academic discourse, innovation scaling has received relatively less attention than the other aspects of the innovation process (e.g., inception of novelty or its diffusion). One field where scaling innovation is particularly popular, however, is in sustainability studies, where scaling and innovation are viewed as key components for sustainable management, development, and growth [16][17][18][19][20]. Though popular, a clear and widely agreed upon definition of scaling remains absent, and so too is a comprehensive theoretical framework for understanding the entire scaling process.…”
Section: Introductionmentioning
confidence: 99%
“…Human resources are a key driver at all levels of system upscaling [26,54]. At the local institutional level, the leaders of farmers' groups can lead discussions about self-motivation for the OCS transformation.…”
Section: Human Resources For An Ocs Scaling-up System In the Mrbmentioning
confidence: 99%
“…A trusted and successful scaling-up system that accommodates the strengths of various systems and approaches to enhance the capacities of actors is needed and still lacking [25]. An efficient scaling-up system can be seen as a mechanism to achieve the effective implementation of development plans and programs [26].…”
Section: Introductionmentioning
confidence: 99%
“…Scaling of a particular technology or technique refers to the increase (e.g. number) or expansion (geographically) of its use (Frake and Messina, 2018;Millar and Connell, 2010). According to Wigboldus et al (2016), scaling may be promoted by a push-approach (promoting the value of specific changes) or a pull-approach (changing enabling conditions).…”
Section: Scaling Of Project-proposed Technology Packagesmentioning
confidence: 99%